THE EFFECT OF HERBAL SUPPLEMENTS ADDITION IN FEED TOWARDS GROWTH PERFORMANCE AND SURVIVAL RATE OF RED TILAPIA (Oreochromis niloticus) USING BIOFLOCS SYSTEM ON PEAT SWAMP WATER - Indah Ismayanti; Rusliadi Rusliadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research aim to determine the optimal dose of additional herbal supplements in feed toward the growth performance and survival rate of red tilapia (Oreochromis niloticus) by using biofloc system on peat swamp water. This research was conducted on January 30-March 10, 2018 at Technical Service Unit (UPT) of Hatchery, Marine and Fisheries Faculty, University of Riau. This research was using experimental method by completely random design (RAL) one factor with three replications. The treatments were: A: 0 mL/kg of feed (control), B: 25 mL/kg of feed, C: 50 mL/kg of feed, and D: 75 mL/kg of feed. The herbal supplements were consisted of turmeric, kencur, temulawak and ginger with Bacillus sp. and yeast (Rhizopus oligosporus). The results showed that a different doses of additional herbal supplements affecting the growth performance and the survival rate of red tilapia usingbiofloc system on peat swamp water. In addition, it also affected the absolute weight growth, absolute length growth, feed efficiency and feed conversion ratio.The optimal dose was at 25 mL/kg of feed as it showed significantly different results compared to control and was not differ significantly at higher doses. So that while being applied in terms of economy, 25 mL/kg  was the most efficient dose, by giving the specific growth rate was 2,33%, survival rate was 80%, absolute weight growth was 3,12 g, absolute length was 2,71 cm, feed efficiency was 89,66% and feed conversion ratio was 1,12.                                                                                      Keyword : herbal supplements, red tilapia, biofloc, peat